How is the role of Digital Leadership and Knowledge Sharing on Performance? An Empirical Study on SMEs in Bandung West Java - Marliana Budhiningtias Winanti (Universitas Dharma Wacana, 2022)
The purpose of this study was to analyze the effect of Digital Leadership on the performance of SMEs and the effect of Knowledge Sharing on the Performance of SMEs in Bandung West Java. The research was conducted using a quantitative approach through a survey. The population of this study were all SMEs employees in Bandung, while the number of samples in this study was 400 people who were selected using simple random sampling. Testing the hypothesis in this study using SEM (Structural Equation Modeling) with the PLS program. The research data was obtained through the distribution of online questionnaires through social media. The results of this study are that Digital Leadership has a positive and significant effect on the performance of SMEs and the variable Knowledge Sharing has a positive and significant effect on Performance SMEs in Bandung West Java.